Antidiabetic potential of triterpenoid saponin isolated from Primula denticulate. (June 2014) - Singh, Sanjay; Farswan, Mamta; Ali, Sadat; Afzal, Muhamad; Al-Abbasi, Fahad A.; Kazmi, Imran; Anwar, Firoz
Abstract Context: Primula denticulate Sm. (Primulaceae), commonly known as drumstick primula, is traditionally used to treat diabetes and urinary disorders. In the present study, a new triterpenoid saponin was isolated. Triterpenoids generally show antidiabetic activity. Considering its traditional use and chemical nature of the molecule, the present study was designed to evaluate the antidiabetic activity. Objective: Antidiabetic activity of triterpenoid saponin (TTS) isolated from P. denticulate. Materials and methods: A new TTS was isolated from the leaf of P. denticulate by column chromatography on CHCl3/MeOH (8.5:1.5) fraction. It was further characterized by using NMR, UV, and IR spectroscopic methods. Ethanol and aqueous extracts of the leaf were also prepared. Antidiabetic study for TTS, ethanol extract, and aqueous extract was carried out in streptozotocin (STZ)-induced diabetic rats at doses of 200, 1000, and 1000 mg/kg body weight, respectively. A toxicity study was also performed. Results: Isolated new TTS molecule was characterized as 3-O[β-d-xylopyranosyl-(1 → 2)-β-d-glucopyranosyl-(1 → 4)-α-l-arabinopyranosyloxy]-16α-hydroxy-13β, 28-epoxy-olean-30-al by NMR, UV, and IR spectroscopic methods. This new TTS was found to be effective in lowering blood-glucose level in the experimental rat model, thus establishing its antidiabetic property (168.8 ± 4.58) when compared with disease control (258.8 ± 0.60). Its LD50 value was found at a dose of 2000 mg/kg. The level of insulin was restored by TTS and ethanol extract up to 31.49 µU/ml and 38.90 µU/ml, respectively, when compared with disease control (18.45 µU/ml). Discussion and conclusion: In conclusion, 3-O[β-d-xylopyranosyl-(1 → 2)-β-d-glucopyranosyl-(1 → 4)-α-l-arabinopyranosyloxy]-16α-hydroxy-3β, 28-epoxy-olean-30-al possesses potential glucose lowering properties, i.e., antidiabetic potential against STZ-induced diabetic rats.